PERSPEKTIF DIGLOSIA SEBAGAI FENOMENA KEBAHASAAN DALAM PENDIDIKAN - Andriyani, Indri; Salsabila, Ririn; Fauzi Rachman, Ichsan (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2024)
This study investigates the phenomenon of diglossia in an educational context with a focus on its influence on language learning and teaching. Diglossia, as a clear separation between high and low language varieties in a society, has affected the dynamics of language in the educational space. The method used in this research is literature or literature review described in descriptive form. Diglossia is a linguistic phenomenon that is often found in the context of education in various countries. This research also reviews the phenomenon of diglossia from two main perspectives, namely positive and negative diglossia as a phenomenon that affects the educational process. It highlights the challenges that arise in managing language diversity in educational contexts, while offering strategies to enhance inclusiveness and effectiveness of language learning. In addition, it provides a conceptual framework for understanding the complex relationship between diglossia and education, and identifies potential research directions to explore this topic further. As such, it contributes to our understanding of the phenomenon of diglossia in educational contexts and provides a foundation for the development of more sustainable and inclusive educational policies and practices.